Industrial Solid Wastes and Their Management in Guilan Province - Mohammadnejad, Shahin (Asian Journal of Chemistry, 2010)
Industries, like other waste sources, are associated with numerous waste-related environmental problems. Guilan province is considered as an important industrial area in northern Iran. There are ca. 1976 industrial units in Guilan province, most of which are located in the outskirts of cities. In the current study an approximation of the quality and quantity of the generated waste in food industry of Guilan province, which is recognized as the largest waste generator industry in the study area in Iran is provided. In present study, questionnaires were used to collect data regarding methods of waste management used in 142 of the food businesses in the area of study. The results of the present research show that putrescibles are the most important waste in this industry. The high percentage of putrescibles in the waste stream (73.7 %) and relatively appropriate physico-chemical characteristics of the waste, suggest the possibility of composting. Additionally, more than 70 % of total non-organic wastes is contributed to packaging processes. There are relatively few industries that implement such correct waste management. Relatively low price of raw materials and lack of efficient penalties in case of inappropriate waste disposal by industries are considered as the major reasons of such deficiency in regional waste management. It is highly recommended that the implementation of such tax policy accompanied by joint management of generated industrial wastes be enforced in the area.